Pulmonary Valve Opening With Two Rotary Left Ventricular Assist Devices for Biventricular Support. Issue 1 (25th July 2017) - Wu, Eric L.; Nestler, Frank; Kleinheyer, Matthias; Stevens, Michael C.; Pauls, Jo P.; Fraser, John F.; Gregory, Shaun D.
Abstract: Right ventricular failure is a common complication associated with rotary left ventricular assist device (LVAD) support. Currently, there is no clinically approved long‐term rotary right ventricular assist device (RVAD). Instead, clinicians have implanted a second rotary LVAD as RVAD in biventricular support. To prevent pulmonary hypertension, the RVAD must be operated by either reducing pump speed or banding the outflow graft. These modes differ in hydraulic performance, which may affect the pulmonary valve opening (PVO) and subsequently cause fusion, valvular insufficiency, and thrombus formation. This study aimed to compare PVO with the RVAD operated at reduced speed or with a banded outflow graft. Baseline conditions of systemic normal, hypo, and hypertension with severe biventricular failure were simulated in a mock circulation loop. Biventricular support was provided with two rotary VentrAssist LVADs with cardiac output restored to 5 L/min in banded outflow and reduced speed conditions, and systemic and pulmonary vascular resistances (PVR) were manipulated to determine the range of conditions that allowed PVO without causing left ventricular suction. Finally, RVAD sine wave speed modulation (±550 rpm) strategies (co‐ and counter‐pulsation) were implemented to observe the effect on PVO. For each condition, outflow banding had higher PVR (97 ± 20 dyne/s/cm 5 higher) for when the pulmonary valve closed compared to reduced speed. In addition, counter‐pulsation demonstrated greater PVO than co‐pulsation and constant speed. For the purpose of reducing the risks of pulmonary valve insufficiency, fusion, and thrombotic event, this study recommends a RVAD with a steeper H‐Q gradient by banding and further exploration of RVAD speed modulation.